Rethinking Research Mentoring: A Tutorial on How and Why to Implement a PhD Student-Mediated Mentorship Model. - McDaniel, Jena; Hessling Prahl, Alison; Schuele, C. Melanie (Perspectives of the ASHA Special Interest Groups, 2022)
Purpose: In this tutorial, we describe the initiation and implementation of a recently developed PhD Student-Mediated Mentorship Model (PS-MMM) used within our lab. In a PS-MMM, PhD students mentor graduate and undergraduate students under the direction of a faculty advisor. The model aims to address the PhD shortage by (a) teaching PhD students to be research mentors to facilitate their success in the early career years and (b) encouraging clinical graduate students to transition into and be successful in research doctoral training. As a third objective, we aim to address the research-practice gap by increasing the research experiences available to undergraduate and clinical graduate students through implementation of a PS-MMM. We provide a step-by-step outline and case examples for initiating and scaling up a PS-MMM. Conclusions: Implementation of a PS-mMm has led to consistent, positive benefits for mentees and mentors within our lab. The observed benefits, feasibility, and flexibility of our PS-MMM support more widespread use of PS-MMMs within other communication sciences and disorders programs.